2006
DOI: 10.1063/1.2358135
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of hard spheres confined in narrow cylindrical pores

Abstract: Finite-size effects in the microscopic structure of a hard-sphere fluid in a narrow cylindrical pore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
3
24
2
Order By: Relevance
“…Using hard body molecular models and hard confining walls it is possible to study purely the geometrical packing effects as the energetic effect are not included in these models. In this regard much attention has been paid to understand the structure and the phase behaviour of several confined systems such as the ordering of hard spheres in narrow cylindrical pore [8,9,10] and slit pores [11] and the helical packing of soft spheres in nanotubes [12,13]. The rapid development of the X-ray techniques makes also possible to study extremely confined fluids, where the particles are confined between two hard walls with thickness just slightly higher than the diameter of the particle [14].…”
Section: Introductionmentioning
confidence: 99%
“…Using hard body molecular models and hard confining walls it is possible to study purely the geometrical packing effects as the energetic effect are not included in these models. In this regard much attention has been paid to understand the structure and the phase behaviour of several confined systems such as the ordering of hard spheres in narrow cylindrical pore [8,9,10] and slit pores [11] and the helical packing of soft spheres in nanotubes [12,13]. The rapid development of the X-ray techniques makes also possible to study extremely confined fluids, where the particles are confined between two hard walls with thickness just slightly higher than the diameter of the particle [14].…”
Section: Introductionmentioning
confidence: 99%
“…water | solid−liquid critical point | carbon nanotube | ice | Widom line T he possibility of the solid-liquid critical point has been reported by computer simulation studies of various systems in quasi-one, quasi-two, and three dimensions that exhibit both continuous and discontinuous changes in thermodynamic functions and other order parameters (1)(2)(3)(4)(5)(6)(7). However, the idea that a solid-liquid phase boundary never terminates at the critical point is still commonly accepted as a law of nature, largely because of the famous symmetry argument (8,9) together with the lack of experimental observations.…”
mentioning
confidence: 99%
“…Later, theoretical quantification for hard-sphere fluids in the very narrow pore was established. 21 In recent years, Gordillo et al 15 observed the onset of freezing shown by a sharp change of the density at certain radii of pores via the same NPT MC method and elucidated that the cause of this behavior is microstructural transformation. With effects of the attractive potential, Koga and Tanaka 7 studied Lennard-Jones ͑LJ͒ confined fluids analogous to argon atoms trapped in single-wall CNT via molecular dynamics ͑MD͒ method.…”
Section: Introductionmentioning
confidence: 99%
“…The former reason is based on several numerical evidences on the existence of the fluidsolid phase transition in both for bulk [11][12][13][14] or confined systems 15 with the absence of attractive interactions. The latter provides the system under effects of dominant influence of entropy, thus leading one to focus on the relation of the phase transition and the structure of confined particles with varying pore sizes.…”
Section: Introductionmentioning
confidence: 99%